2006
DOI: 10.1103/physrevb.73.085121
|View full text |Cite
|
Sign up to set email alerts
|

Band-structure parameters and Fermi resonances of exciton-polaritons in CsI and CsBr under hydrostatic pressure

Abstract: Most alkali halides crystallize in the fcc sodium chloride structure. In contrast, with the exception of CsF, the Cs-halides form the simple cubic cesium chloride (CsCl) structure at ambient conditions and they have a substantially different electronic structure than other alkali halides; in particular, they have several nearly degenerate electronic levels near the Brillouin zone center. Highly resolved Three-Photon Spectroscopy (TPS) measurements allow direct observation of the near band edge structure and, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Theoretical models of Br-atom desorption from the α-CsBr (CsCl-type lattice) and β-CsBr (rocksalt-type lattice) surfaces induced by 6.4 and 7.9 eV ns laser pulses have been discussed in ref . The experimental band gap of β-CsBr is 7.3 eV, and the first singlet exciton peak occurs at 6.96 eV . The position of the surface exciton peak is not established experimentally, but our calculations predict it at ∼6.4 eV .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Theoretical models of Br-atom desorption from the α-CsBr (CsCl-type lattice) and β-CsBr (rocksalt-type lattice) surfaces induced by 6.4 and 7.9 eV ns laser pulses have been discussed in ref . The experimental band gap of β-CsBr is 7.3 eV, and the first singlet exciton peak occurs at 6.96 eV . The position of the surface exciton peak is not established experimentally, but our calculations predict it at ∼6.4 eV .…”
Section: Resultsmentioning
confidence: 77%
“…The experimental band gap of β-CsBr is 7.3 eV, 47 and the first singlet exciton peak occurs at 6.96 eV. 29 The position of the surface exciton peak is not established experimentally, but our calculations predict it at ∼6.4 eV. 30 This suggests that 6.4 eV photons can excite surface excitons but are unlikely to excite bulk excitons.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The poor agreement between the LCAO (HF and DFT) calculations and the experiment shows that these calculations Smith and Pong (1975) 7.90 7.30 6.50 (b) Nosenzo and Reguzzoni (1979) 8.01 7.15 5.98 (c) Lipp et al (2006) -7.20 6.14 (iii) Available theory (a) Satpathy (1986) 5.28 4.16 3.51 (b) Boer and Groot (1998) -4.10 -(c) Mei et al (2000) 5.10 5.20 4.20 LMTO: Linear muffin tin orbital method SCAD: Self consistent atomic deformation.…”
Section: Compton Profilesmentioning
confidence: 94%
“…Recently, Mei et al (2000) vibration properties of alkali halides including CsX and compared their results with the other available data. Lipp et al (2006) have reported the band structure parameters of CsBr and CsI using three-photon excitation spectroscopy. Few other high-pressure phase transition studies on CsX compounds have also been reported by different workers (Nardelli et al, 1992;Schlosser and Ferrante, 1993;Tsujimoto et al, 1996).…”
Section: Introductionmentioning
confidence: 99%